DETEKSI MOLEKULER Mycobacterium tuberculosis DI DAHAK CARA POLYMERASE CHAIN REACTION - P. B. Notopuro; J. Nugraha; H. Notopuro (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
tuberculosis is a chronic infectious disease which is found in developing and developed country. It is one of community healthproblems which become priority in national and international health programs. Microbiologic examination is used to establish thediagnosis of tuberculosis beside clinical examination and radiologic examination. Conventional microscopic and culture examinationhave many limitation ie: such as for example low sensitivity, specificity and need a lot of time. New Molecular technique gives morevalue in sensitivity, specificity and the time for examination. the aim of this study was to know the diagnostic value of PolymeraseChain Reaction for detection of Mycobacterium tuberculosis in sputum. the sputum was collected from twenty eight patients suspectedtuberculosis based on the clinical and radiological examination. the study was performed from September 2006 until July 2007. Wedid the conventional culture technique as a diagnostic gold standard and molecular technique to detect the Mycobacterium tuberculosisin the sputum. For molecular technique, we used Polymerase Chain Reaction (PCR) with a set of IS6110 region primer which is specificfor the Mycobacterium tuberculosis Complex. the sensitivity of PCR with IS6110 region primer is 100% (very high), specificity is 82.4%(high), positive predictive value is 89.7% and negative predictive value is 100%. there was statistically no significant difference betweenthe result of PCR and conventional culture method. Based on the result, the Polymerase Chain Reaction examination with primer IS6110region primer can be used as the screening tool for tuberculosis infection, while the clinician waits for culture result.